Hydrolytically stable ZIF-8@PDMS core–shell microspheres for gas–solid chromatographic separation. Issue 16 (2nd February 2016) - Srivastava, Manju; Roy, Prasun Kumar; Ramanan, Arunachalam
Abstract : Metal organic frameworks (MOFs) with exceptionally high surface areas, shape selectivity and availability of multiple active sites are suitable materials to serve as solid stationary phase for chromatographic applications. Abstract : Metal organic frameworks (MOFs) with exceptionally high surface areas, shape selectivity and availability of multiple active sites are suitable materials to serve as solid stationary phase for chromatographic applications. Packed columns filled with conventionally prepared MOFs result in high pressure drops and low column efficiency, mainly due to the presence of small irregular shaped crystals and broader size distribution. In this paper, we report the successful utilization of the hydrolytically stable microcrystalline zinc imidazolate (ZIF-8), a well-known MOF immobilized on a thermally stable polymer i.e., polydimethylsiloxane (PDMS) for application as a stationary phase towards gas–solid chromatographic separations. A gas chromatography (GC) column (2 m × 2.5 mm) packed with the ZIF-8@PDMS core–shell microspheres demonstrate efficient separation of liquid and gas mixtures including xylene isomers and natural gas mixtures. We also successfully used the stationary phase for quantification of ethanol concentration in aqueous samples; the column did not undergo any structural change suggesting its excellent hydrolytic stability.